Analysis of the Effectivenesss of Bicycle Lanes in Metro City - Havis, Muhammad Al; Purba, Aleksander; Herianto, Dwi; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
AbstractBicycles are an sustainable mode of transportation because they do not produce exhaust gas. Motor vehicle exhaust gas is one of the causes of global warming. The bicycle lane facilities in Metro City aim to get Metro City as an friendly city to cyclists. This study aims to find out the level of effectiveness of bicycle lanes in Metro City. The research methods used for the effectiveness of bicycle lanes are the BCI (Bicycle Compatibility Index) method which refers to the reference (Harkey et al., 1998), the BLOS (Bicycle Level Of Service) method which refers to the reference (Sprinkle Consulting Inc., 2007) and the Guttman method which refers to the reference (Guttman, 1944). The BCI and BLOS model methods result for bicycle lanes in metro city on average get a C rating which means the road conditions are quite suitable (quite safe and comfortable) for cyclists. The obtained of C rank is inseparable from the high volume of traffic and inadequate road body width in some roads. Guttman's method for bike lanes in Metro City resulted in a percentage of 55,55% which means it is suitable for use. Although it is appropriate, but there is still something that needs to be improved on the facilities and there needs to be a policy related to the use of bicycles and bicycle lanes.Keywords: effectiveness, bicycle lane, Metro City, Bicycle Compatibility Index, Bicycle Level of Service, Guttman